1997
DOI: 10.1111/j.1600-051x.1997.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety of enamel matrix derivative (EMDOGAIN®) in the treatment of periodontal defects

Abstract: The aim of the present clinical trial was to test tolerability during 2 treatments with EMDOGAIN in a large number of patients. An open, controlled study design in 10 Swedish specialist clinics was chosen, with a test group of 107 patients treated with EMDOGAIN in connection with periodontal surgery at 2 surgical test sites per patient. The procedures were performed 2 to 6 weeks apart on one-rooted teeth with at least 4 mm deep intraosseous lesions. A control group of 33 patients underwent flap surgery without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
139
0
27

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(176 citation statements)
references
References 18 publications
10
139
0
27
Order By: Relevance
“…Based on the previous study, (12)(13)(14)(15) it was assumed that the size of the EMD-induced effect on linear alveolar bone growth 36 weeks after administration was 0.81 mm. The estimated size of the rhFGF-2-induced effect from the pooled data in Study A and previous studies (9,10) was about 1.05 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous study, (12)(13)(14)(15) it was assumed that the size of the EMD-induced effect on linear alveolar bone growth 36 weeks after administration was 0.81 mm. The estimated size of the rhFGF-2-induced effect from the pooled data in Study A and previous studies (9,10) was about 1.05 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of studies and the fact that EMD is known to have growth factor-like effects on different cell lines, EMD is said to be clinically safe (8)(9)(10). However, assessments of clinical safety have been limited to evaluations of the capability of porcine enamel proteins to induce immunological reactions or local postoperative symptoms, such as pain or sensitivity in the teeth involved, which have been studied both in vitro and in vivo (8)(9)(10)(11)(12)(13). There is abundant evidence regarding the effects of EMD on periodontal tissues, including its stimulation of periodontal and gingival fibroblast cell migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The apical border of the notch (N) to the cewhich supports the hypothesis on clinical usefulness of EMP. The safety and effectiveness of EMP for improving the repair of periodontal bone defects have been noted in humans and other animals (17,23), and a histological study reported that the true periodontal regeneration ability was maintained (12). The adjuvant use of EMP in regeneration therapy aimed at the formation of cementum, alveolar bone and periodontal membrane structure is expected.…”
mentioning
confidence: 99%